SOSIALISASI LITERASI KEUANGAN UNTUK RUMAH TANGGA - Yulia Yunita Yusuf; Anisatun Humairah Rais; Andi Faisal; Adriansyah Adriansyah; Ahmad Nasiruddin Musaddiq Rahman (Universitas Ichsan Sidenreng Rappang, 2025)
This community service activity aims to improve financial literacy among housewives at Almadinah Islamic School Makassar. Through seminars and interactive discussions, participants were equipped with basic knowledge of financial planning, budgeting, cash flow recording, and expense control. The activity successfully demonstrated an increase in participants' understanding and a growing desire to apply financial literacy concepts more systematically. Despite challenges such as conventional habits and limited time, participants showed strong motivation to change. This activity made a tangible contribution to raising awareness and enhancing financial skills at the household level.